Clever : leading your smartest, most creative people - Goffee, Robert; Jones, Gareth, 1951 August 21- (Boston, Mass. : Harvard Business Press, 2009)
Leading clever people can be enormously challenging, yet doing so effectively is the key to your organization's sustained success. Lively and engaging, this book provides the ideas, practices, and examples you need to create an environment where your most brilliant people can flourish.
Understanding clever people -- What can leaders do? -- The anatomy of clever teams -- Breaking the code of clever teams -- Contours of the clever organization -- The future of clever organizations.
Includes bibliographical references (pages 169-172) and index.
Description based on print version record.
Keywords: Creative ability in business; Teams in the workplace; Leadership; Employee motivation; Führung; Kreativität; Mitarbeiter; Motivation; Creative ability in business; Employee motivation; Leadership; Teams in the workplace; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books